Logistic optimization in tourism networks - Armindo Frias; Jo\~ao Cabral; Álvaro Costa (European Regional Science Association (ERSA), 2015)
Tourism doesn?t depend on a specific resource and enable the integration of local populations and economies, generating benefits that have a stronger effect on regional development. Literature main stream identifies tourism as one of the activities with high impact on the development and for many regions, especially for small remote territories. In our natural laboratory, the Azores Island of S\~ao Miguel, an important share of tourists identifies adventure, leisure and touch with nature, as the main reasons for the visit. In this sense, footpaths are an important tool to promote environmental and social education, encouraging the observation and improving the knowledge about the nature and endorsing greater respect for our heritage. Its use can contribute to the satisfaction of tourists, promoting tourism and the region's development during their movements on the tourism network, tourists appreciate different types of attractions and need the support of a set of facilities. Tourist decisions aren?t always done in a rational way, emotions add even more complexity to the human decision process. The movement of tourists within a destination and the level of satisfaction that they can achieve, depends on factors related to tourist characteristics, like the time budgets, preferences or destination knowledge, and destination features related to attractions characteristics or accessibility level. In order to offer relevant tourism products, stakeholders need to understand how tourists take their decisions and what their preferences are. That knowledge will be able to build optimized tourism products that meet the tourists? preferences and facilities that allow the use of the network in an optimal way by the different tourist profiles. The existence of a mathematical model that incorporates the main factors that explain the movement of independent tourists within a destination, in a dynamic way, will make possible the creation of an adaptable software tool. This tool will meet the specific needs of tourism and the needs of regional business and government, according to their endogenous features, improving the optimization of investments in transport networks and the infrastructure that supports tourism related activities. This article is based on the authors? previous research and identifies the relevance of tourism for regional development and finds the main tourists? mobility criteria on the studded territory, using as main support the footpath network. Additionally, recognises the necessary modelling process and developed the foundation for the building of the mathematical model that explains the movement of tourists within the destination, making possible a future adaptable software tool.
Keywords: R41; R12; R32; 330; logistics; facility localization; networks; tourism; regional development